Investment lumpiness and the role of net worth: evidence from Europe. (20th February 2013) - Chichti, Jamel E.; Mansour, Walid
This paper examines investment lumpiness under incentive restrictions. When financial frictions enter the picture into the neoclassical framework, investment is no longer smooth due to the lump-sum costs that the firm incurs when raising costly external finance. Whited (2006) shows that the firm finds it optimal to not invest to avoid paying such costs. Investment is accordingly characterised by lumpiness. We estimate a binomial logit model for the investment spike (i.e., large investment) using a sample of nine OECD European countries. We find that our proxies for net worth and future growth opportunities impact positively the probability of investment spike. The paper further extends the analysis to encompass some behavioural aspects.